Marketing Strategy of Coca-Cola - Kolesnik, Nadezhda; Halík, Jaroslav, 1961-; Štěrbová, Ludmila, 1957-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2021)
The aim of this bachelor thesis is to analyze the marketing strategy of The Coca-Cola Company and to identify its key crucial factors of success. Besides that, the thesis analyzes typical Coca-Cola customer and the most recognized campaigns of Coca-Cola, as well as the possible reason of it. Afterwards, several recommendations for the company are provided. The thesis is divided in two parts: theoretical and practical, that are divided into sub-chapters with their own goal. The theoretical part provides necessary terms and definitions later used in the thesis. The practical part is devoted to the analysis of the company and its marketing strategies. Afterwards, its results are represented, as well as recommendations, mainly regarding the further improvement of marketing strategy. Finally, the thesis outlines conclusion and author’s own opinion. The main approach of the thesis is analytical analysis, including collection of data (primary, secondary and literature review), its analysis and synthesis of crucial factors. According to the major results of the research, The Coca-Cola Company uses the following marketing strategies: “glocal” and marketing mix strategies. The factors of success of The Coca-Cola Company are not only “glocal” strategy, but also weak power of suppliers, successful customer value-based pricing strategy, and strong promotion mix. In terms of typical customer of Coca-Cola beverage, it is a woman in the age range of 18 to 29, studying and working part time with low- or middle-income. She buys it because of taste, mostly in the supermarket and less than once a month. She prefers Cola over Pepsi and considers it a high-quality product for an average price. Further, the most recognized campaigns are “Share a Coke” and “Holidays are Coming”, since they are either highly personalized, unique, or evoking emotions.
Vedoucí práce: Jaroslav Halík
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses